AFFIRMATIVE ACTION’S MEDIATION ROLE ON THE IMPACT OF GLOBALISATION ON THE PROLETARIANS IN ZIMBABWE - Fore, Cleopas; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2022)
Globalisation debate in recent years is characterised with trade literature, growth and formation of multinational companies, the internationalisation motive, market liberalisation and the impact of these on nation states’ labour markets (Giddens, 2004). Zimbabwe as a nation is not exempted from the impact of globalisation on its labour relations. Literature review identified that to curb the adverse effects of globalisation, Zimbabwe adopted the use of affirmative action policies, which were received with mixed feelings of criticisms and appreciations. This article sought to understand the impact of globalisation on affirmative action and establish the extent to which affirmative action policies ameliorate the negative effects of globalisation. A qualitative paradigm was adopted. Data was gathered through the use of interviews and participants memoirs. Results were analysed by usingf both Nvivo 10 and manual coding. Results showed that either globalisation has an impact on affirmative action through inspiring the promulgation of policies or labour legislation that eradicates discrimination, or it can stifle some policies that deter globalisation. The article recommended that to ensure fairer globalisation there is need to use affirmative action policies to ameliorate discriminations occasioned by globalisation on Zimbabwe’s employment relations. Affirmative action policies need to be properly discussed and shared by all social partners to increase the chance of success in their implementation. With openness and shared goals, affirmative action policies and laws can help to achieve fairer globalisation.